Strategy for Developing Civil Servant Competencies in the Badung Regency Government - Triantara, I Kadek Rafi Yoga; Veratiani, Gek Aris (Universitas Indonesia Mandiri, 2026)
The capacity building of State Civil Apparatus (ASN) is an important factor in achieving professional and quality public services.The achievement of the performance of ASN Indonesia is still confronted by many problems that refer to effectiveness, professionalism and responsiveness in public service.This state tells that development of the ASN compentence must be systemic and sustainable. The purpose is to examine the approach developing ASN competency in Badung Regency Government through the Civil Service and Human Resources Development Agency. The research applies a qualitative method and adapts case study design. The methods of data collection are documentary study and regulations on the subject in question, scientific literature. Descriptive qualitative analysis is used with strategic management models and SWOT analysis.Findings indicate that ASN competency development in Badung Regency is driven by robust regulations, local government commitment and the strategic role of BKPSDM.However, there are still limitations, including expensive cost of budgeting and a brief track for training.Based on the results of this study, it is recommended that local civil service positions be further developed according to merit principles and bureaucratic reform in Badung Regency. This research concludes: that the development for ASN competence in the district government of Badung with regard to improving training quality, using technology and ongoing evaluation